2004
DOI: 10.1080/05698190490501995
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation into the Temperature Profile of a Compliant Foil Air Bearing

Abstract: Public reporting burden for this collection of Information is estimated to average 1 liour per response, including tlie time for reviewing instructions, searcfiing existing data sources, gatfiering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…The startstop cycles act as a polishing wear mechanism between the asperities of the top foil and coating, resulting in a smooth, glossy, oxide-rich surface on the coating and the development of a solid lubricant layer on the foil surface (ref. 14). After the break-in cycles the final coating surface roughness was approximately 0.2 μm.…”
Section: Test Apparatus/proceduresmentioning
confidence: 92%
See 1 more Smart Citation
“…The startstop cycles act as a polishing wear mechanism between the asperities of the top foil and coating, resulting in a smooth, glossy, oxide-rich surface on the coating and the development of a solid lubricant layer on the foil surface (ref. 14). After the break-in cycles the final coating surface roughness was approximately 0.2 μm.…”
Section: Test Apparatus/proceduresmentioning
confidence: 92%
“…According to reference 13 it is estimated that 80 percent of this heat is conducted away via the shaft and bearing surface, which can increase bearing internal temperatures 200 °C higher than the surrounding environment (ref. 14).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the temperature rise slope during the rotor speed coast down was bigger than the slope during the rotor speed up. Radil, et al, (2004) performed a series of tests to determine the internal temperature profile in a bump foil air bearing operating at room temperature under various load and speed conditions. Tests were conducted at loads from 9 to 222 N and speeds ranged from 20 to 50 krpm.…”
Section: Experimental Studies Of Thermal Characteristicsmentioning
confidence: 99%
“…Bearings operating near their load capacity limit may provide static and dynamic stiffness values one to two times higher than this range but such operation is not typical and can suffer from thermal instability and rapid failure (Ref. 15).…”
Section: Foil-gas Bearings-performance Characteristicsmentioning
confidence: 99%